PHARMACOEPIDEMIOLOGICAL STUDY OF DOCTORS HABITS IN PRESCRIPTIONS OF ANTIHYPERTENSIVE DRUGS IN TOWN OF OREL - G. I. Shvets; S. V. Povetkin (Столичная издательская компания, 2016)
Aim. To compare prescriptions of antihypertensive drugs in town of Orel with these in Russia in the whole.Material and methods. 23 cardiologists and 78 internists of Orel town were questioned about antihypertensive drug prescriptions in 2006.Results. ACE inhibitors, diuretics, beta-blockers, calcium channels antagonists were prescribed in order of popularity decreasing as mono- or combined therapy. About 70 % of doctors prescribed pharmacotherapy, which cost 100 to 500 rubles per months. Not rational combinations were prescribed in 4,7% of cases. Only 55,4% of respondents used blood pressure level less than 140/90 mm Hg as a target one.Conclusion. Antihypertensive drug prescription for mono- or combined therapy was in accordance to modern guidelines but in the some cases did not meet them.